Recent advances in high-capacity free-space optical and radio-frequency communications using orbital angular momentum multiplexing. (28th February 2017) - Willner, Alan E.; Ren, Yongxiong; Xie, Guodong; Yan, Yan; Li, Long; Zhao, Zhe; Wang, Jian; Tur, Moshe; Molisch, Andreas F.; Ashrafi, Solyman
Abstract : There is a continuing growth in the demand for data bandwidth, and the multiplexing of multiple independent data streams has the potential to provide the needed data capacity. One technique uses the spatial domain of an electromagnetic (EM) wave, and space division multiplexing (SDM) has become increasingly important for increased transmission capacity and spectral efficiency of a communication system. A subset of SDM is mode division multiplexing (MDM), in which multiple orthogonal beams each on a different mode can be multiplexed. A potential modal basis set to achieve MDM is to use orbital angular momentum (OAM) of EM waves. In such a system, multiple OAM beams each carrying an independent data stream are multiplexed at the transmitter, propagate through a common medium and are demultiplexed at the receiver. As a result, the total capacity and spectral efficiency of the communication system can be multiplied by a factor equal to the number of transmitted OAM modes. Over the past few years, progress has been made in understanding the advantages and limitations of using multiplexed OAM beams for communication systems. In this review paper, we highlight recent advances in the use of OAM multiplexing for high-capacity free-space optical and millimetre-wave communications. We discuss different technical challenges (e.g. atmospheric turbulence and crosstalk) as well as potential techniques to mitigate such degrading effects. This article is part of the themed issue 'Optical orbital angular momentum'.